Diffusion Dynamics of Energy-Efficient Renovations Causalities and Policy Recommendations - Müller, Matthias otto. (Lecture Notes in Energy,, 2013)
Accelerating the diffusion of energy-efficient renovations is a key policy lever in order to reduce the environmental impact of buildings. This book provides a broad, systemic perspective on the causes of the diffusion of energy-efficient renovations in Switzerland and policy recommendations for accelerating the diffusion process. Specifically, the book provides a description of the societal problem situation within which the diffusion process takes place and an analysis of the actors involved. It provides a detailed explanation of the causes of the diffusion process that synthesizes insights from the engineering, economics, marketing, sociology, communication studies and political science literature. It employs the System Dynamics methodology to simulate the diffusion process and analyze policy levers. The book proposes two regulations and a sketch of a business model as particularly promising public policy interventions. It concludes with an outline of a generic theory of the diffusion of sustainable technologies. .